2019
DOI: 10.5098/hmt.12.26
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic and Thermal Performance Twisted Tape Insert Provided in Heat Exchanger Tubes: A Review

Abstract: This work presents a review of the research recent results concerning the augmentation of hydrodynamic and thermal performance of various twisted tape inserts in heat exchanger tubes. The thermal and hydrodynamic correlations for various twisted tape elements have been summarized. A comparative study of thermal and hydrodynamic performance of numerous twisted elements has also been reported to understand the result of applications of twisted tape inserts in heat exchanger tubes. The literature review found tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
0
1
0
Order By: Relevance
“…For practical applications, researchers found PATT as an effective passive tape inset to save energy and operating costs. Datt et al (2019) reviewed the works of different researchers related to the hydrodynamic and thermal performance of inserts as TT. Researchers observed the performance of an insert is affected by the twist pitch and the twist angle.…”
Section: Experimental Studies On Ttmentioning
confidence: 99%
“…For practical applications, researchers found PATT as an effective passive tape inset to save energy and operating costs. Datt et al (2019) reviewed the works of different researchers related to the hydrodynamic and thermal performance of inserts as TT. Researchers observed the performance of an insert is affected by the twist pitch and the twist angle.…”
Section: Experimental Studies On Ttmentioning
confidence: 99%
“…A thorough review work was presented by Datt et al [12] concerning recent studies on augmentation of hydrodynamic and thermal performance of various twisted tape inserts in heat exchanger tubes. Thermal and hydrodynamic correlations for various twisted tape elements were summarized that included a comparative performance of multiple twisted tapes in a single conduit.…”
Section: Introductionmentioning
confidence: 99%
“…They observed that the system performance factor relies on different parameters including refrigerant mass velocity, vapor quality, and geometry of inserts. More discussions regarding the performance of twisted tape inserts in heat exchangers are provided by Kumar et al [20], Bucak and Yilmaz [21], Dewan et al [22], Liu and Sakr [23], and Garg et al [24].…”
Section: Introductionmentioning
confidence: 99%